SOCIAL DETERMINANTS OF HEALTH AFFECTING UTILIZATION OF MATERNAL HEALTH SERVICES IN AFRICA: A NARRATIVE REVIEW - Ronald MUSIZVINGOZA (Rojan GÜMÜŞ, 2020)
Despite improvements in maternal health, Sub-Saharan Africa countries still experience high maternal deaths. The provision of quality maternal health services has been adopted as a key strategy to reduce maternal mortality. However, low utilization rates and inequitable access to maternal health services across the region continue to hinder progress. The objective of the study was to synthesize evidence on the social determinants of maternal health services utilization in sub-Saharan Africa. A narrative review of peer-reviewed articles published between 2010 and 2019 was conducted. Peer-reviewed published studies were electronically searched from databases using search terms covering access and use, social determinants, maternal health services and sub-Sharan Africa. Data were qualitatively analyzed, and results summarized using the World Health Organization's Social Determinants of Health Framework. A total of 36 studies were reviewed. The study identified several social determinants that act as barriers or facilitators to maternal health utilization. Factors identified include socioeconomic status, educational level, women's autonomy, urban residence, gender norms, geographical proximity, access to media, high social capital, social support, exposure to media and functional health system. Maternal healthcare utilization is still low in sub-Saharan Africa and it reflects disparities according to socioeconomic status and rural/urban residence. Programs and interventions to improve maternal health should target social determinants that create inequalities in society.